2022
DOI: 10.2196/35318
|View full text |Cite
|
Sign up to set email alerts
|

Text Messages to Support Caregivers in a Health Care System: Development and Pilot and National Rollout Evaluation

Abstract: Background Although there are many interventions to support caregivers, SMS text messaging has not been used widely. Objective In this paper, we aimed to describe development of the Department of Veterans Affairs (VA) Annie Stress Management SMS text messaging protocol for caregivers of veterans, its pilot test, and subsequent national rollout. Methods The stress management protocol was developed with text m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…(5) Specifically, we found that technologies can empower caretakers to become more involved and informed in their loved one's care. (14) Future research should explore how technologies can be integrated into clinical workflows without being viewed as disruptive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(5) Specifically, we found that technologies can empower caretakers to become more involved and informed in their loved one's care. (14) Future research should explore how technologies can be integrated into clinical workflows without being viewed as disruptive.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, post-implementation, we met with hospitalists and nurse leaders to solicit feedback, using focus group methodology to identify how we could make enhancements (1620). Those enhancements are discussed in the companion article.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation